To Correlate the Oral Health-related Quality of Life Between Smokers and Smokeless Tobacco Users Among 35-44 Years Age Group Attending Teerthanker Mahaveer Dental College and Research Centre, Moradabad, Uttar Pradesh, India - Harshita Pandey; Pradeep Tangade; Vikas Singh; Ankita Jain; Rangoli Srivastava; Mukund Sharma (Wolters Kluwer Medknow Publications, 2024)
Background: Tobacco use poses severe health risks globally, affecting both young people and adults. It is highly addictive and a major contributor to various diseases, including cancer. This research at Teerthanker Mahaveer Dental College and Research Centre (TMDC and RC), Moradabad, focused on participants aged 35-44, highlighting the urgent need to address tobacco-related issues for public health and economic well-being. Aim: This study assesses the occurrence of smokers and smokeless tobacco and analyzes its correlation with the oral health-related quality of life (OHRQoL) among participants. Materials and Methods: A prevalence study was substantiated at TMDC and RC, Moradabad, involving 640 participants aged between 35 and 44 years. Informed assent was obtained from all participants. Sociodemographic information was collected, and their oral mucous lesions were assessed using the World Health Organization form. In addition, participants completed a validated Hindi version of the Oral Health Impact Profile-14 questionnaire to evaluate their OHRQoL. Results: The study revealed a higher prevalence of tobacco usage among males compared to females. Furthermore, the prevalence of smoking was established to be greater than that of smokeless tobacco. Consequently, a statistically apparent association was recognized between smokers and their OHRQoL, as well as between users of smokeless tobacco and their OHRQoL. However, no association was established between smokers, smokeless tobacco users, and OHRQoL when considering the significance value. Conclusion: The study indicates that individuals aged 35-44 years who use either smoked or smokeless tobacco experience similar impacts on their OHRQoL. Encouraging regular dental examinations, facilitating access to tobacco cessation programs, and extending support for individuals to sustain tobacco-free lifestyles are indispensable strategies for amplifying oral health outcomes besides the overall quality of life among individuals aged 35-44.